USING SUGGESTOPEDIA TECHNIQUE AS AN ALTERNATIVE WAY IN TEACHING READING COMPREHENSION - Dewi Kartika Sari (Jurnal Dosen Universitas PGRI Palembang)
AbstractGetting information through reading activities becomes one of the most important ways. Reading is the most important skill for students to learn, because their success or failure in school or in society depends on their ability to read. Reading involves an interaction between a specific typeof text or written material and a reader who has a purpose for reading that is related to the type of text and the context of the reading situation. Understanding reading material needs a specific reading strategy. The strategy should facilitate the comprehension of the students who want to read effectively. One of the techniques which can be used is Suggestopedia. suggestopedia is a teaching technique which is based on a modern understanding of how the human brain works andhow we learn most effectively. This technique on reading comprehension is designed to give students the learning environment relaxed, subdued, with low lighting and soft music playing in the background.Key words: reading activities, strategy, suggestopedia technique.